2010
DOI: 10.1111/j.1651-2227.2009.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between 6‐min walk test and exercise stress test in healthy children

Abstract: SMWT distance is significantly correlated with the eVO2 obtained during the EST. This indicates that SMWT is also one of the predictive markers for EST performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 15 publications
(20 reference statements)
6
26
0
7
Order By: Relevance
“…(8,23,24) The 6MWDs achieved in the first and second tests were similar in both of our groups, indicating the reproducibility of the test, as reported in other studies. (3,8,12) Repeating the 6MWT is recommended by the American Thoracic Society.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…(8,23,24) The 6MWDs achieved in the first and second tests were similar in both of our groups, indicating the reproducibility of the test, as reported in other studies. (3,8,12) Repeating the 6MWT is recommended by the American Thoracic Society.…”
Section: Discussionsupporting
confidence: 72%
“…More vigorous exercise and severe forms of COPD can cause major reductions in SpO 2 and reduced exercise tolerance. (22,24) The self-reported sensation of dyspnea was greater in the control group than in the CF group. Healthy children might not have the ability to measure dyspnea, because this condition is unknown in their experience.…”
Section: Discussionmentioning
confidence: 95%
“…Correlation between V o 2 from CPET and 6MWT in healthy children 18 and correlation between CPET and 6MWT in patients with IPAH 2 have been reported by others, but no correlation between 6MWT predicted V o 2 and measured V o 2 has been reported. However, Ross et al 19 attempted to predict peak V o 2 from 6MWD in patients with different cardiopulmonary disorders and reported poor prediction accuracy for assessing individuals for clinical purposes.…”
Section: Discussionmentioning
confidence: 93%
“…[13][14][15][16] Greater pre-transplantation 6MWD also correlates with shorter intensive care unit stays after pediatric lung transplantation. 17 Correlation between V o 2 from CPET and 6MWT in healthy children 18 and correlation between CPET and 6MWT in patients with IPAH 2 has been reported by others but not prediction of V o 2 peak from 6MWT. Ross et al 19 attempted to predict peak V o 2 from 6MWD in patients with different cardiopulmonary disorders, suggesting poor prediction accuracy for assessing individuals for clinical purposes.…”
Section: Doi: 101097/hcr0000000000000174mentioning
confidence: 99%
“…Correlation between estimated VO₂ from CPET and 6MWT in healthy children (Limsuwan, Wongwandee, & Khowsathit, 2010) and correlation between CPET and 6MWT in patients with IPAH (Oudiz et al, 2006a) has been shown by others. The correlation between 6MWT and measured VO₂ has not been shown.…”
Section: Studymentioning
confidence: 98%